Immediate Experience – Contradictio in Adjecto? Strategies for Reflecting on the Immediacy of Experience by M. Henry and T. Sodeika - Norus, Laurynas (Problemos, 2024)
This article considers the problem of immediacy of experience in the philosophy of Michel Henry and Tomas Sodeika. The article argues that the tension between the requirements of descriptiveness and performativity in phenomenological philosophy emerges particularly vividly in the work of these philosophers. Both philosophers understand the immediacy of experience as an oxymoronic structure that cannot be directly described, requiring very specific efforts and ingenuity from the phenomenologist in order to convey it to the reader. The article analyses and compares the strategies for reflecting on the immediacy of experience in the work of the authors in question. Both philosophers, while emphasising the imperative of performativity in phenomenology, face the intractable contradiction between experience mediated by its description and life that, strictly speaking, cannot be mediated. This raises the question not only about the limitations of phenomenology, but also, more generally, about the limitations of philosophy itself.